Innovación en emprendimientos periodísticos y de comunicación frente a las nuevas tendencias digitales (Monográfico) - Escobar, Ana Paulina (2020)
In the world, journalism and communication entrepreneurships have been innovating in the face of digital era. Also known as startups, these entrepreneurships reveal in general the wish to start a project, to innovate, to renew. In this article, we reflect one of the concepts that describe the entrepreneurships scenario, such as digital appropriation and mutations of work dynamics; likewise, we explore the experience of two projects: the portal of narrative journalism La Barra Espaciadora and the communication agency Orion. When studying them, we have observed common characteristics as well as specific particularities, which together reveal changes in both journalism and communication in the digital era.